PENGARUH MIKRO EKONOMI TERHADAP HARGA SAHAM PADA PT. INDUSTRI JAMU DAN FARMASI SIDO MUNCUL TBK. PERIODE 2014-2023 - Astuti, Eni Puji; Aziz, Muhamad Sailan Abdul (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
The purpose of this research is to determine the effect of microeconomics on stock prices at PT. Industri Jamu dan Farmasi Sido Muncul Tbk. during the period 2014 to 2023. The method used in this study is a descriptive quantitative approach using secondary data in the form of company financial reports. The samples analyzed is the financial report of PT. Industri Jamu dan Farmasi Sido Muncul Tbk. 2014 - 2023. Data analysis was performed using SPSS software version 30. The analysis techniques used include descriptive analysis tests, classical assumption tests, multiple linear regression, and hypothesis tests. The results of this study indicate that the Earnings Per Share variable has a significant partial effect on stock prices (T value 7.383 > T table 2.365 and a significance value of 0.001 <0.05), and the Price to Book Value variable also has a significant effect on stock prices (T value 23.748 > T table 2.365 and a significance value of 0.001 <0.05). Simultaneously, the variables Earnings Per Share and Price to Book Value have a significant effect on stock prices with a calculated F value of 331.779 > F table 4.737 and a significance value of 0.001 < 0.05.